Politics and Emotions in Historical Perspective (KULT_online, 2014)
The 16 essays in this volume emerged out of a lecture series and an interdisciplinary conference on "Politics and Emotions" during summer term 2011 at the Freie Universität Berlin. Interdisciplinary perspectives explore the relation of individual and collective emotions. The shared focus on the political dimension of emotions in the Early Modern and Modern periods results in a transepochal approach to the history of emotions.